LIBRARY PROFESSIONALS' PERSPECTIVE ON THE IMPACT OF SOCIAL MEDIA IN ENHANCING LEARNING AND LIBRARY SERVICES IN ALIGARH DIVISION'S HIGHER EDUCATIONAL INSTITUTIONS - Gupta, Shalini; Fatima, Shahwar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The advent of social media has revolutionized communication and engagement across various sectors, and academic libraries are no exception. The integration of social media into library services has significantly transformed how libraries interact with their users, making library resources more accessible and improving engagement with users. Social media platforms such as Facebook, LinkedIn, Twitter, YouTube, and Instagram have provided library professionals with powerful tools to reach a vast audience, promote digital resources, share academic materials, and foster communication between users and library staff. These platforms are no longer just about casual interaction; they have evolved into vital spaces for professional development, research sharing, and engagement with the academic community.